HEALTH WATER MANAGEMENT SYSTEM IN URBAN AREA - Agustyarum Pradiska Budi; Junaedi Junaedi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Conservation of water resources in Indonesia is based on the management of springs on a large scale or in terms of water production. The approach that is often used is management from the demand side so that the mindset of the people is still trapped that water resources are free goods that can be taken without having to renew them again. This research tries to achieve direct community participation to participate in realizing and managing water resources directly. Community participation techniques use advice on implementing policies to improve water resources. The policies offered include infiltration wells, biopori, and reforestation. The policy offer is the right alternative for households/communities directly. The purpose of this study is divided into 3, namely knowing the level of community WTP, knowing the variables that affect the WTP and preference analysis of alternative policy choices. The results of the analysis show that the WTP level of the city of Surakarta is still low, which is equal to WTP ≤ Rp. 50,000. Policy variables can influence the level of willingness to pay by 42.60% compared to other variables only able to influence by 15.95% calculated using multinomial logistic regression. The results of the Analytical Hierarchy Process (AHP) analysis show that the ranking 1 weighting is the infiltration well policy.